MENINGKATKAN PENGUASAAN BENTUK GEOMETRI MENGGUNAKAN KEGIATAN MOZAIK PADA ANAK USIA DINI - Khaerani Mondani Az Zahra; Ghina Wulansuci (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2019)
Mastery of geometric shapes in children can be seen from how the child is able to mention and understand geometric shapes, connect and sort geometric shapes, as well as show, express, and tell the results of work in the form of geometry. Mastery of geometric shapes in children can be improved by activities that make children active, one of which is mosaic activities. Mosaic activity is the excitement of sticking to pieces made of certain material. This study aims to improve the mastery of geometric shapes in early childhood using mosaic activities. The method used is a quantitative method with a quasi-experimental approach. Obtained an average gain value of the experimental class 0.820, while the control class is 0.053, which means mastery of the geometric shapes of the experimental class children who are given more mosaic activities compared to the control class which is only given conventional activities. Therefore, mosaic activities can improve the mastery of geometric shapes in children.